Astrocytes expressing Vitamin D‐activating enzyme identify Parkinson's disease. (15th February 2022) - Mazzetti, Samanta; Barichella, Michela; Giampietro, Federica; Giana, Angelica; Calogero, Alessandra M; Amadeo, Alida; Palazzi, Nicola; Comincini, Alessandro; Giaccone, Giorgio; Bramerio, Manuela; Caronni, Serena; Cereda, Viviana; et al.
Abstract: Introduction: Astrocytes are involved in Parkinson's disease (PD) where they could contribute to α‐Synuclein pathology but also to neuroprotection via α‐Synuclein clearance. The molecular signature underlying their dual role is still elusive. Given that vitamin D has been recently suggested to be protective in neurodegeneration, the aim of our study was to investigate astrocyte and neuron vitamin D pathway alterations and their correlation with α‐Synuclein aggregates (ie, oligomers and fibrils) in human brain obtained from PD patients. Methods: The expression of vitamin D pathway components CYP27B1, CYP24A1, and VDR was examined in brains obtained from PD patients (Braak stage 6; n  = 9) and control subjects ( n  = 4). We also exploited proximity ligation assay to identified toxic α‐Synuclein oligomers in human astrocytes. Results: We found that vitamin D‐activating enzyme CYP27B1 identified a subpopulation of astrocytes exclusively in PD patients. CYP27B1 positive astrocytes could display neuroprotective features as they sequester α‐Synuclein oligomers and are associated with Lewy body negative neurons. Conclusion: The presence of CYP27B1 astrocytes distinguishes PD patients and suggests their contribution to protect neurons and to ameliorate neuropathological traits. Abstract : The vitamin D‐activating enzyme CYP27B1 identifies a subpopulation of astrocytes in PD patients. CYP27B1 positive astrocytes sequester α‐Synuclein oligomers and contact Lewy body negative neurons. In conclusion, the presence of these astrocytes distinguishes PD patients and suggests their contribution to protect neurons that could ameliorate neuropathological traits.